Composting Humboldt: How might Donna Haraway's posthumanism enrich an understanding of Wilhelm von Humboldt's Bildung? - Louis Waterman-Evans (University of Aberdeen, School of Education, 2022)
This conceptual research aims to reconfigure Wilhelm von Humboldt's Bildung considering Donna Haraway's 'compostist' posthumanism. Three aspects of Humboldt's Bildung are identified and analysed: individuality, unity of nature and mind, and holistic knowledge. Posthumanism is narrowed to Haraway's 'compostist' conception, with the identified aspects: making kin as 'oddkin' and recognising Indigenous Knowledges. The main conceptual argument draws on these analyses to recast Humboldt's Bildung in the following ways: 1) individuality is understood in terms of ecological relationality; 2) the human mind and 'nature' 'become-with' one another in more dynamic interplay; and 3) holistic knowledge is revised to incorporate knowledges beyond 'Western' epistemologies. The paper aspires to open up a new horizon for Humboldt's Bildung, understood through Haraway's 'compostist' posthumanism. The resulting 'compostist' posthumanist Bildung has the potential to shape our formation to be compatible with living on a damaged planet and to lay the preliminary conceptual groundwork for addressing some of our times' most complex questions.